2020
DOI: 10.1186/s13068-020-01797-7
|View full text |Cite
|
Sign up to set email alerts
|

Studies on sugar transporter CRT1 reveal new characteristics that are critical for cellulase induction in Trichoderma reesei

Abstract: Background Trichoderma reesei is an ascomycete fungus that has a tremendous capability of secreting extracellular proteins, mostly lignocellulose-degrading enzymes. Although many aspects of the biology of this organism have been unfolded, the roles of the many sugar transporters coded in its genome are still a mystery with a few exceptions. One of the most interesting sugar transporters that has thus far been discovered is the cellulose response transporter 1 (CRT1), which has been suggested to be either a sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…The Crt1 protein is now recognized as a high affinity transporter of cellobiose and lactose, similar to its analog in N. crassa Cdt1 and is believed to play a critical role in the cellulase induction signaling cascade. [ 158 ].…”
Section: Engineering Of Transporters and Effect On Gene Expressionmentioning
confidence: 99%
“…The Crt1 protein is now recognized as a high affinity transporter of cellobiose and lactose, similar to its analog in N. crassa Cdt1 and is believed to play a critical role in the cellulase induction signaling cascade. [ 158 ].…”
Section: Engineering Of Transporters and Effect On Gene Expressionmentioning
confidence: 99%
“…The most significantly upregulated gene was gene ID 69957 or Tr69957 (log2 fold change = 6.15), reported as a cellobiose, mannose and xylose transporter [34]. ID 3405 or crt1, reported as a cellobiose and sophorose transporter which plays a key role in the cellulolytic signaling process [35,36], showed the highest gene expression level of the significantly expressed transporters. ID 50894 or str1, reported as a transporter induced by pentose, ID 121482 or str2, reported as a transporter with broad substrate specificity [37], and ID 79202 and 77517, reported as a lactose transporter [38], were all upregulated in PC-3-7ΔtubB.…”
Section: Gene Ontology Enrichment Analysismentioning
confidence: 99%
“…Whereas a number of T . reesei sugar transporters have been characterized regarding their in vitro activities in transporting sugars released from lignocellulose hydrolysis ( Saloheimo et al, 2007 ; Ivanova et al, 2013 ; Zhang et al, 2013 ; Huang et al, 2015 ; Sloothaak et al, 2016 ; Nogueira et al, 2018 ; Havukainen et al, 2020 , 2021a , b ), relatively few of them have been found to be involved in the regulation of lignocellulolytic enzyme production. In particular, the cellobiose transporter Crt1 plays an essential role in activation of cellulase genes in T .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the cellobiose transporter Crt1 plays an essential role in activation of cellulase genes in T . reesei , regardless of the inducing carbon sources used ( Ivanova et al, 2013 ; Zhang et al, 2013 ; Havukainen et al, 2020 ). Deletion of crt1 , however, does not compromise but improves xylanase production ( Zhang et al, 2013 ), implicating a difference in sugar transporter-involved induction mechanisms between cellulase and xylanase genes.…”
Section: Introductionmentioning
confidence: 99%